CORRUPTION AND INVESTMENT: EVIDENCE FROM SOUTHEAST ASIA - Ferry Ardiyanto (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2011)
This paper employs market potential, market size, macroeconomic, corruption, democracy, labor, and human capital variables to investigate the relationship between foreign direct investment and corruption in Southeast Asia. he efficient grease hypothesis argues that corruption can increase investment as it acts as grease money that enables firms to avoid bureucratic red tape, thus improving economic efficency. Consequently, fighting corruption would be a counterproductive. However, this may not be the case. Empirical results shows that worsening of corruption in host economies leads to a reduced inflow of foreign direct investment. A one-point increase in corruption level is associated with approximately 26,5 percent reduction in investment. Therefore, corruption is considered as grabbing hand rather than a helping hand for investment, sanding instead of greasing the wheels of commerce, and reducing rather than increasing economic efficiency.